CONSTRUCTION OF BOUGUER GRAVITY ANOMALY MAP IN THE EAST VIETNAM SEA AND ADJACENT AREA - Que, Bui Cong; Dung, Tran Tuan; Tram, Le (Vietnam Journal of Marine Science and Technology, 2008)
All the gravity data sources in the East Vietnam Sea, which are from the shipboard surveys of Vietnam and foreign countries in the past 50 years to present along with satellite gravity, have been collected. The gravity data have been integrated, analyzed to construct a united Bouguer gravity map at scale of 1:1,000,000 for the whole East Vietnam Sea and adjacent area. The map is constructed in the Mercator WGS-84 projection and digitalized by GIS technique. The homogeneity and accuracy of the map are suitable to scale of 1: 1,000,000 and can be used to different purposes